2016
DOI: 10.1186/s13100-016-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

The endonuclease domain of the LINE-1 ORF2 protein can tolerate multiple mutations

Abstract: BackgroundApproximately 17 % of the human genome is comprised of the Long INterspersed Element-1 (LINE-1 or L1) retrotransposon, the only currently active autonomous family of retroelements. Though L1 elements have helped to shape mammalian genome evolution over millions of years, L1 activity can also be mutagenic and result in human disease. L1 expression has the potential to contribute to genomic instability via retrotransposition and DNA double-strand breaks (DSBs). Additionally, L1 is responsible for struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 58 publications
(119 reference statements)
4
19
0
Order By: Relevance
“…5e ). Importantly, LINE-1 cytotoxicity has been previously reported to depend on endonuclease (EN) and reverse transcriptase (RT) activities 8 - 10 , and we confirmed that expression of LINE-1 with inactivating EN and RT mutations is less toxic than wildtype (WT) LINE-1 ( Extended Data Fig. 8 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…5e ). Importantly, LINE-1 cytotoxicity has been previously reported to depend on endonuclease (EN) and reverse transcriptase (RT) activities 8 - 10 , and we confirmed that expression of LINE-1 with inactivating EN and RT mutations is less toxic than wildtype (WT) LINE-1 ( Extended Data Fig. 8 ).…”
Section: Resultssupporting
confidence: 83%
“…Many studies have focused on host factors that alter retrotransposition efficiency or on the functional effects of acquired LINE-1 insertions; fewer have focused on cellular effects of LINE-1 expression 6 - 10 . LINE-1 is known to be toxic, but the mechanisms underlying its toxicity are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While we did discover the importance of the Y1180 residue to Alu retrotransposition, it is worth noting that this region of the ORF2p can tolerate individual mutations at other conserved positions. This is similar to the recently described mutagenic tolerance of the ORF2p EN domain (Kines et al 2016). However, there are several important differences between the two.…”
Section: Discussionsupporting
confidence: 88%
“…To assess the impact of mutation of these amino acids on ORF2p expression, untagged ORF2 constructs with individual amino acids E1165, D1171, Y1180, Y1189 K1190, or Y1232 changed to A were transiently transfected into HeLa cells. Total cell lysate of these cells was subjected to Western blot analysis using ORF2p antibodies specific to amino acids 960-973 (Kines et al 2014;Christian et al 2016a;Kines et al 2016). All constructs expressed their corresponding protein ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation